2021
DOI: 10.1080/14787210.2022.1990756
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin: an exploratory study of antiviral mechanism and host-pathogen interaction in COVID-19

Abstract: Introduction COVID-19, a dreadful pandemic that has impacted human life like no other pathogenic invasion, has claimed the lives of over 100 million people. The need for effective treatment strategies is still a subject of intense research considering the rapidly evolving genome and continental diversity. Indomethacin is administered mostly as co-treatment for affected patients as a non-steroidal anti-inflammatory drug (NSAID). However, the underlying mechanism of action is unresolved. This study … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…Direct evidence for the antiviral efficacy of indomethacin, but not of aspirin, against SARS-CoV-2 was provided in cellular models and in vivo in an infected canine model [ 90 ], suggesting that the effect is independent of anti-inflammatory action. A very recent review has shown, with system biology-based modeling, that the action of indomethacin against SARS-CoV-2 depends on the fact that prostaglandin synthetase is related to the action of some structural proteins, so that the inhibition of the former blocks the function of the latter, which are involved in the replication of viral RNA [ 91 ].…”
Section: Indomethacin As a Promising Nsaidmentioning
confidence: 99%
“…Direct evidence for the antiviral efficacy of indomethacin, but not of aspirin, against SARS-CoV-2 was provided in cellular models and in vivo in an infected canine model [ 90 ], suggesting that the effect is independent of anti-inflammatory action. A very recent review has shown, with system biology-based modeling, that the action of indomethacin against SARS-CoV-2 depends on the fact that prostaglandin synthetase is related to the action of some structural proteins, so that the inhibition of the former blocks the function of the latter, which are involved in the replication of viral RNA [ 91 ].…”
Section: Indomethacin As a Promising Nsaidmentioning
confidence: 99%
“…PGs trigger the release of pro-inflammatory cytokines, activation of Th cells (Th1 and Th17), recruitment of immune cells, and increase expression of pro-inflammatory genes (Ogletree et al 2022 ). PGs are chiefly inhibited by non-steroidal anti-inflammatory drugs (NSAIDs) through the blocking of cyclooxygenase enzymes (COXs), which are involved in the synthesis of PGs (Shekhar et al 2022 ). NSAIDs reduce inflammation by selective or non-selective blocking activity of COX2 or COX1/2, respectively (Shekhar et al 2022 ).…”
mentioning
confidence: 99%
“…PGs are chiefly inhibited by non-steroidal anti-inflammatory drugs (NSAIDs) through the blocking of cyclooxygenase enzymes (COXs), which are involved in the synthesis of PGs (Shekhar et al 2022 ). NSAIDs reduce inflammation by selective or non-selective blocking activity of COX2 or COX1/2, respectively (Shekhar et al 2022 ). COX2 is stimulated and up-regulated during SARS-CoV-2 infection (Ogletree et al 2022 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations